2012
DOI: 10.1590/s0100-06832012000600025
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade de macronutrientes e rendimento de milho em latossolo fertilizado com dejeto suíno

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
1
26
0
8
Order By: Relevance
“…Cassol et al (2012) observed a similar effect studying the application of swine biofertilizer on corn grown without irrigation (rainfed cropping).…”
Section: Resultsmentioning
confidence: 71%
“…Cassol et al (2012) observed a similar effect studying the application of swine biofertilizer on corn grown without irrigation (rainfed cropping).…”
Section: Resultsmentioning
confidence: 71%
“…Both PS and SF were broadcast on the soil surface on the straw of winter crops. The PS was distributed by a hose with a jet, connected to a pressurized tank, and soluble fertilizer by hand (Cassol et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…All crops were sown with a no-till seeder, consisting of a front disc gang and double-disc furrower (Cassol et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The application of pig manure as slurry (PS) increases the levels of N, P, K, Ca and Mg in the soil (Scherer et al, 2007;Veiga et al, 2012b) and in the crops (Choudhary et al, 1996;Cassol et al, 2012;Sartor et al, 2012;Scherer et al, 2012). Due to the low content of nutrients present in this manure (Scherer et al, 1996), the use of large volumes is usually necessary to provide enough amounts of plant nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low content of nutrients present in this manure (Scherer et al, 1996), the use of large volumes is usually necessary to provide enough amounts of plant nutrients. Cassol et al (2012) found that corn production increased with doses of PS in an Oxisol and estimated that 90% of the maximum crop yield would be obtained by applying 84 m 3 ha -1 . Doses of PS recommended by the Commission of Chemistry and Soil Fertility of the South Section of the Brazilian Society of Soil Science (SBCS, 2004) to supply nutrients to crops is based on the nutrient content in the soil, the nutritional requirements of the crop, the concentration of the nutrient in the manure and the efficiency ratio of each nutrient.…”
Section: Introductionmentioning
confidence: 99%